Effects of early recurrence and extra-PV triggers on long-term recurrence after catheter ablation for atrial fibrillation. (3rd October 2022) - Park, Y; Yu, H T; Kim, T H; Uhm, J S; Joung, B; Lee, M H; Pak, H N
Abstract: Background: Although early recurrence (ER) within 3 months after atrial fibrillation (AF) catheter ablation (AFCA) was recently reported to be a reliable predictor of late recurrence (LR), the mechanism is not clear. Purpose: We explored the characteristics of patients with ER and compared the long-term late recurrence (LR) pattern depending on the existence of extra-pulmonary vein trigger (ExPV-trigger). Methods: Among 3643 patients who underwent de novo AFCA, we included 1249 patients (59.2±11.0 years old, 31.3% persistent AF) who underwent isoproterenol provocation and regular follow-up over three years after AFCA. We evaluated the risk factors for ER and compared the patients with ER alone (10.1%), LR alone (16.6%), and ER+LR (15.9%), and the outcome of repeat procedure. Results: Overall ER (ER alone and ER+LR) was independently associated with persistent AF (OR 1.58 [1.16–2.14], p=0.003), extra-PV triggers (OR 2.80 [1.90–4.13], p<0.001), and empirical extra-PV ablation (OR 1.54 [1.15–2.07], p=0.004). Overall LR (LR alone and ER+LR) risk was significantly higher in the ER with ExPV-trigger group than in ER without ExPV-trigger or no ER groups (Log-rank p<0.001). The rhythm outcome of the second procedure did not differ between ER+LR and LR alone groups (Log-rank p=0.160), but was worse in the ER+LR ExPV-trigger than in ER+LR without ExPV-trigger or LR alone groups (Log-rank p=0.005). Conclusion: ER was independently associated with LR after de novo AFCA. ExPV-trigger played crucial roles in ER and LR after de novo AFCA and worse rhythm outcome after redo AFCA. Funding Acknowledgement: Type of funding sources: None.